Awareness on health programs in Kubza Village of Mokokchung District, Nagaland: A case study - *, Lendina; Naga, Moses M. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Health is one factor which everyone needs to take care of. Health programmes that are launched by the Government needs to be made aware to all the rural people. This article gives a survey report on awareness of some selected health programmes and the sources of information used by the rural people to get information on health programmes. Awareness on health programmes was found to be very low. More awareness should be given to the rural people on health programmes.